Impact of Ablation during Index Hospitalization on All-Cause Mortality in Patients with Typical Atrial Flutter: Insights from National Multicenter Database - Amer, Muhammad; Annie, Frank H.; Adhikari, Shubash; Mukherjee, Debabrata (International Journal of Angiology, 2023)
Background We sought to assess the impact of ablation during index hospitalization (IH) on all-cause mortality (ACM) in patients presenting with newly diagnosed typical atrial flutter (tAFL) as compared with patients without ablation, irrespective of optimal rate or rhythm control medications.Methods We identified patients with newly diagnosed tAFL in the TriNetX Research Network between January 20, 2010, and January 20, 2021. Using International Classification of Diseases, 10th revision (ICD-10) codes, patients were stratified into those who had undergone ablation during IH and those who did not undergo the procedure. Results were assessed using propensity score matching (PSM) analysis as well as Kaplan–Meier curves.Results A total of 12,986 (N) patients (aged 35–85 years) met our inclusion criteria. Of those, 3,665 had undergone ablation during IH compared with 9,321 patients who did not. Patients in the ablation group (mean age 64.3 ± 10.1 years) had a higher prevalence of hypertension (80 vs. 78.3%, p = 0.02), respectively. PSM created two well-matched groups of 3,652/3,652 patients each with an ACM of ablation of 4.5 versus 7.8% (p = 0.01) at 6 months, 6.6 versus 11.4% (p = 0.01) at 12 months, and 14.5 versus 20.9% (p < 0.001) at 36 months of follow-up. Survival data were confirmed through Kaplan–Meier analysis using a log-rank test.Conclusion From a large, federated, multicenter population database, we report significant survival benefit of ablation during IH in patients presenting with new tAFL diagnosis. Kaplan–Meier mortality curves confirmed survival advantage with ablation at 6, 12, and 36 months of follow-up in this cohort.
Keywords: ablation; all-cause mortality; typical atrial flutter; cardiovascular mortality